2014
DOI: 10.1002/pon.3550
|View full text |Cite
|
Sign up to set email alerts
|

Australian men with cancer practice complementary therapies (CTs) as a coping strategy

Abstract: Complementary therapies have the potential to facilitate coping with cancer, independent of any measurable physiological benefit. Our findings suggest that when clinicians engage in conversations about CTs use, they should consider the type of coping strategy employed by their patient. Such information may enhance the efficacy of some interventions (e.g., meditation) and also provide for an opportunity to discuss patients' expectations concerning CTs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…); and preference for self‐management (Klafke et al . ). However, although recent studies have identified the symptom burden and supportive care needs of prostate cancer survivors and the factors that contribute to these (Smith et al .…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…); and preference for self‐management (Klafke et al . ). However, although recent studies have identified the symptom burden and supportive care needs of prostate cancer survivors and the factors that contribute to these (Smith et al .…”
Section: Introductionmentioning
confidence: 97%
“…In particular, men with prostate cancer are less likely to discuss their social and emotional concerns with health care providers compared to women with breast cancer (Forsythe et al 2013). Reasons for men's hesitancy to seek help may include under-reporting of emotional, physical or sexual concerns (Kunkel et al 2000;Holden et al 2006;Bernat et al 2015;Yousaf et al 2015); somatisation of mental health symptoms (Kockler & Heun 2002;Fiske et al 2009); self-reliance and a desire to maintain a sense of normalcy (Gray et al 2000;Yousaf et al 2015); concerns about burdening others (Gray et al 2000); discomfort or embarrassment (Yousaf et al 2015); being less well educated or unaware (Dunn et al 1999); and preference for self-management (Klafke et al 2014). However, although recent studies have identified the symptom burden and supportive care needs of prostate cancer survivors and the factors that contribute to these (Smith et al 2000;McDowell et al 2010McDowell et al , 2011Bernat et al 2015;Gavin et al 2015;Watson et al 2015), patterns of help-seeking in this population to address unmet needs are less well described (Neese et al 2003;Hyde et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…In some studies, participants also reported that prayer with others (e.g., in a group or with a family member) was particularly helpful [26, 27, 32, 34, 36, 38, 39]. In one study, participants also turned to the saints for support in their prayers [34].…”
Section: Resultsmentioning
confidence: 99%
“…Awareness, compassion, receptiveness, and adaptiveness have been considered communication skills useful to overcome these barriers . Moreover, it has been suggested that when clinicians engage in conversations about CTs use, they could consider it as a coping strategy employed by the patient (e.g., diet modification as a problem‐focused coping, meditation as an emotion‐focused coping, and prayer or spiritual healing as a meaning‐based coping) .…”
Section: Discussionmentioning
confidence: 99%